Three-year follow-up of the impact of Kumamoto Earthquake on acute myocardial infarctions: An interrupted time series analysis - Sunao Kojima; Takehiro Michikawa; Kenichi Tsujita (American Heart Journal Plus, 2023)
Study objective: This study aimed to investigate whether the incidence of acute myocardial infarction (AMI) and subsequent outcomes over the three years after the Kumamoto earthquake differed from the underlying trend before the earthquake. Design: Quasi-experimental design. Setting: Twenty-one institutions participating from the Kumamoto Prefecture and capable of receiving AMI patients and performing coronary angiography and interventions. Participants: In total 6553 consecutive patients with AMI between 2013 and 2019 were included in this study. Interventions: Interrupted time series analysis. Main outcome measure(s): AMI incidence and following cardiac events after the earthquake. Results: The rate ratio (RR) for AMI incidence after the earthquake was 1.12 (95 % confidence interval [CI]: 1.00–1.25) with reference to that before the earthquake. AMI rates increased among people with diabetes mellitus (RR: 1.20, 95 % CI: 1.01–1.44), those with current smoking (RR: 1.27, 95 % CI: 1.03–1.56), and those with a body mass index >25 kg/m2 (RR: 1.27, 95 % CI: 1.06–1.52). Increased number of AMI patients with onset-to-door time >12 h (RR: 1.46, 95 % CI: 1.02–2.08), a high Killip class on hospital admission (RR: 1.37, 95 % CI: 1.13–1.67), and unperformed emergent coronary angiography (RR: 1.40, 95 % CI: 1.02–1.91) were frequently observed after the earthquake, which may affect following in-hospital cardiac events (RR: 1.49, 95 % CI: 1.03–2.15). Conclusions: The Kumamoto earthquake had an impact on the increase in the incidence of AMI and the following in-hospital cardiac outcomes. Emergency medical care should be ensured in such a way that high-risk patients are managed as usual, especially immediately after earthquake.